Intensitas Penyakit Pembuluh Kayu (Ppk) Pada Areal Budidaya Tanama Kakao Di Desa Benggaulu Kecamatan Dapurang Kabupaten Pasangkayu Provinsi Sulawesi Barat - Suaib S, Ismail; Lakani, Irwan; Isrun, Isrun (Mitra Sains, 2022)
The aim of this research is to measure the intensity of wood vein disease and the level of soil fertility in areas of cocoa land affected by the disease and to determine the relationship between the level of maintenance (sanitation) of cocoa and the development of wood disease attacks. The analysis was carried out by calculating the incidence of disease and disease severity using the disease incidence and severity formula and the data was carried out using a simple variable correlation test to see the relationship between the sanitation level of cocoa plants. and the development of PPK disease. The results of disease incidence calculations show that land two (2) has the highest incidence of PPK disease at 69.33% and the lowest disease incidence is found in land four (4), namely 42.67%. Meanwhile, the highest level of PPK disease severity was found on land 2 at 29.47% and the lowest level of disease severity was found on land 4 at 13.73%. The results of the bivariate correlation test (r) show the person value correlation value r = 0.992 with a significance value (5%) = 0.008, which means that sanitation has a very close relationship with the development of wood disease.